Rencana Rute dan Stasiun Transportasi Monorel Kota Makassar - Muhammad Darul Fikri Idris; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
Makassar city is one of the main centers of economic growth in Eastern Indonesia, has population growth rate of 7% per year, resulting in high intensity of population activity that has an impact on demand for transportation services. The ownership of private vehicles increase and the growth of the road networks are constant, which ultimately has an impact on traffic jams. The research aimed to determine the monorail routes and stations according to the demand for people trips. This research was conducted from September 2019 to January 2020 (4 months). The research obtained from primary data, the existing road network and the condition of public transportations, and secondary ones, such as: Makassar City Regional Spatial Plan (RTRW), population data, land use pattern, and movement pattern. The research was done by using qualitative and quantitative description analysis, origin to destination matrices, and spatial analysis (desire line and network analyst). The research found that there are four monorail routes network planning according to demand of people movement, which the three routes planning have been documented in Makassar City RTRW, and the new route that has found is the route that serve the movement in Barombong – Losari Beach – Port.